The effect of glenohumeral plane of elevation on supraspinatus subacromial proximity. (5th October 2018) - Lawrence, Rebekah L.; Sessions, William C.; Jensen, Megan C.; Staker, Justin L.; Eid, Aya; Breighner, Ryan; Helwig, Nathaniel E.; Braman, Jonathan P.; Ludewig, Paula M.
Abstract: Shoulder pain is a common clinical problem affecting most individuals in their lifetime. Despite the high prevalence of rotator cuff pathology in these individuals, the pathogenesis of rotator cuff disease remains unclear. Position and motion related mechanisms of rotator cuff disease are often proposed, but poorly understood. The purpose of this study was to determine the impact of systematically altering glenohumeral plane on subacromial proximities across arm elevation as measures of tendon compression risk. Three-dimensional models of the humerus, scapula, coracoacromial ligament, and supraspinatus were reconstructed from MRIs in 20 subjects. Glenohumeral elevation was imposed on the humeral and supraspinatus tendon models for three glenohumeral planes, which were chosen to represent flexion, scapular plane abduction, and abduction based on average values from a previous study of asymptomatic individuals. Subacromial proximity was quantified as the minimum distance between the supraspinatus tendon and coracoacromial arch (acromion and coracoacromial ligament), the surface area of the supraspinatus tendon within 2 mm proximity to the coracoacromial arch, and the volume of intersection between the supraspinatus tendon and coracoacromial arch. The lowest modeled subacromial supraspinatus compression measures occurred during flexion at lower angles of elevation. This finding was consistent across all three measures of subacromial proximity. Knowledge of this range of reduced risk may be useful to inform future studies related to patient education and ergonomic design to prevent the development of shoulder pain and dysfunction.